Pengaruh Dosis Vermikompos terhadap Pertumbuhan Produksi dan Serapan N & P Tanaman Mentimun (Cucumis sativus L.) pada media asal Dua Kedalaman Tanah Ultisol - Yuka, Muhammad Farchan; Niswati, Ainin; Hendarto, Kus (Jurnal Penelitian Pertanian Terapan, 2017)
The productivity of cucumber in ultisol soil is commonly low due to problems of soil fertility and physical soil properties. Organic fertilizers like vermicompost can be used as a solution to improve soil fertility. The study was conducted from August to December 2015 in the Integrated Field Laboratory, Faculty of Agriculture, University of Lampung. The study used a randomized block design (RAK) factorial 2 x 4. The first factor was the dose of vermicompost 0%, 10%, 20%, 30%, and the second factor, soil depth 0-20 cm (S1) and 20-40 cm (S2). Variance of homogeneity test was performed using Bartlett test and test of additivity by Tukey's test. Variance data and differences in the median value of treatment tested with Honestly Significant Difference (HSD) at 5% level of confident. Correlation test was performed between plant growth by pH, organic C, total-N, P-available, uptake of N and P plant at 5% level of confident. The results showed that (1) Application of vermicompost at a dose of 30% is best for fruit weight, fruit diameter, the weight of dry stover and pH of the soil, uptake of N and P uptake cucumber plants. (2) The number of female flowers cucumber plants and soil pH is higher at a depth of 0-20 cm compared with a depth of 20-40 cm Ultisol Natar. (3) There is no interaction between soil depth and vermicompost on growth, the production of cucumber plants, soil pH, uptake of N and P uptake by cucumber plants. Keywords: Cucumber, uptake of N and P, vermicompost